2013
DOI: 10.1007/s00586-013-3016-x
|View full text |Cite
|
Sign up to set email alerts
|

Pure percutaneous pedicle screw fixation without arthrodesis of 32 thoraco-lumbar fractures: clinical and radiological outcome with 36-month follow-up

Abstract: Purpose To evaluate the outcome of pure percutaneous fixation of unstable single level fractures at the thoracolumbar junction (A1 to B2 Magerl/AO Spine). Method Neurological intact patients were included in a 2-year prospective study (follow-up 36 months). Two groups were considered: the group in which additional short bilateral screws in the fractured vertebra were placed was called lordorizing screw group (LSG), the other was called non lordorizing screw group (nLSG). Clinical outcome was evaluated using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
(44 reference statements)
3
21
0
1
Order By: Relevance
“…The use of percutaneous fixation is studied on a case-by-case basis. 19,20 Percutaneous fixation can be performed in normal bone or in fragile bone; in the latter case, cemented screws can provide valuable contribution. 12,13 Short-and Middle-Term Results…”
Section: Indications Of Vertebroplasty and Other Vertebral Augmentatimentioning
confidence: 99%
“…The use of percutaneous fixation is studied on a case-by-case basis. 19,20 Percutaneous fixation can be performed in normal bone or in fragile bone; in the latter case, cemented screws can provide valuable contribution. 12,13 Short-and Middle-Term Results…”
Section: Indications Of Vertebroplasty and Other Vertebral Augmentatimentioning
confidence: 99%
“…The average score achieved in the SF-36 psychological score was 56.22, which exceeds the scores from the back pain population (48.25) and the normal population (51.54). 17 In the study of Schmidt et al, of the 76 patients with type A fractures who were treated with minimally invasive instrumentation, 32 patients (42.1%) had no substantial discomfort and pain as compared before surgery. Six months following surgery, 58 patients (76.3%) met their expectations or were highly pleased by their individual postoperative results.…”
Section: Discussionmentioning
confidence: 98%
“…The fixation of burst fractures by posterior approach is generally conducted with posterolateral fusion or posterior fusion. However, other authors 8,10,26,30,33,35,36) reported good results by using open or percutaneous pedicle screw fixation only without fusion.…”
Section: Introductionmentioning
confidence: 99%
“…There are only few literatures available which describes percutaneous screw fixation for thoracolumbar burst fracture 8,26,35,36) . Spinal canal integrity, sagittal balance and anterior column intactness are very important for successful outcome in this type of injury.…”
Section: Introductionmentioning
confidence: 99%